2009
DOI: 10.1007/s12274-009-9034-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of WS2 and MoS2 fullerene-like nanoparticles from solid precursors

Abstract: Inorganic fullerene-like WS 2 and MoS 2 nanoparticles have been synthesized using exclusively solid precursors, by reaction of the corresponding metal oxide nanopowder, sulfur and a hydrogen-releasing agent (NaBH 4 or LiAlH 4 ), achieved either by conventional furnace heating up to ~900 °C or by photothermal ablation at far higher temperatures driven by highly concentrated white light. In contrast to the established syntheses that require toxic and hazardous gases, working solely with solid precursors permits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 41 publications
3
48
0
1
Order By: Relevance
“…Its shock-resistant ability is even better than that of carbon nanotubes which possess excellent mechanical properties [6]. Besides, the anti-shock ability of IF-WS 2 is twice that of boron carbide and silicon carbide, which are currently widely used as anti-shock materials [8][9][10][11].…”
mentioning
confidence: 99%
“…Its shock-resistant ability is even better than that of carbon nanotubes which possess excellent mechanical properties [6]. Besides, the anti-shock ability of IF-WS 2 is twice that of boron carbide and silicon carbide, which are currently widely used as anti-shock materials [8][9][10][11].…”
mentioning
confidence: 99%
“…under a vacuum of 10 À4 torr. The activated carbon served two purposes: (a) providing high solar absorbance, which allows the rapid achievement of ultra-high temperatures (up to $3000 K), [26][27][28][29][30][31] and (b) serving as a high-temperature reducing agent for residual oxygen and moisture trapped in the ampoules. The ampoules were irradiated for 10 min using a solar ablation system described and illustrated in previous studies 26,27,29,30 where solar beam radiation is concentrated by a factor of $15 000 in a high numerical aperture Gregorian telescope, delivering $120 W onto a focal spot of $8 mm 2 inside the reactor ampoule.…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] It has proven capable of producing the type of continuously high-temperature reactor environments (target temperatures up to $3000 K with extensive ultra-hot strong-gradient annealing regions) suitable for the synthesis of a panorama of inorganic nanomaterials, though limited to low yields. [26][27][28] Recently however, it was shown that by adding Pb as a catalyst, solar ablation can provide a high-yield synthesis for INT from MoS 2 , MoSe 2 , WS 2 and WSe 2 , 29 and can produce unique PbSSnS 2 mis¯t superstructures. 30 Here, we use solar ablation to generate new, stable, previously unreported types of IF-Pb@GaS and INT-Pb@GaS core-shell nanoparticles, where the Pb core is sheathed by seamless GaS layers.…”
Section: Introductionmentioning
confidence: 99%
“…Зокрема, ведуться роботи над створенням твердих радіаційностійких електропровідних антифрикційних матеріалів адаптованих для експлуатації в широкому діапазоні температур, нанокристалічних добавок до промислових олив для поліпшення їх триботехнічних характеристик; водневих сенсорів; високоанізотропних напівпровідникових наноматеріалів для перетворювачів енергії (хімічних джерел струму, фотоелектрохімічних перетворювачів сонячної енергії, сонячних батарей); каталізаторів; фотокаталізаторів в області водневої енергетики, теплоізоляційних наноматеріалів з наднизькими значеннями теплопровідності, магнітних наноматеріалів. В даний час значна увага приділяється вивченню можливостей отримання фулереноподібних структур на основі шаруватих халькогенідів металів [1], які очікувано знайдуть своє застосування як тверді лубриканти [2], або компоненти нанокомпозитних структур [3,4]. Інша перспективна ніша застосування таких систем -електродні матеріали для літій-йонних джерел струму, що працюють на інтеркаляційному принципі [5].…”
Section: вступunclassified